Do Working Papers Increase Journal Citations? Evidence from the Top 5 Journals in Economics - Klaus Wohlrabe; Constantin Bürgi (Center for Economic Studies and Ifo Institute (CESifo), 2020)
Does it pay off in terms of citations to issue an article as a working paper before it is published in a refereed journal? We show empirically that the answer is yes, using 3167 articles published in five of the top journals in economics between 2000 and 2010. The effect is an around 25% higher number of citations on average across the investigated journals.
Keywords: A10; A12; 330; working paper; peer review; citations; RePEc; preprint